Effect of Injecting Local and Commercial Chicken Eggs with Arginine Amino Acid on the Chick Weight, Bursa of Fabricius Characteristics, and Estrogen Levels - Aziz, Shangaberry Rawf; Ameen, Questan Ali; Aziz , Nasrin Hassan; Shaker , Ahmed Sami; Mohammed , Mohammed Sardar; Jalal , Bakhan Jalil (American Journal of Biology and Natural Sciences, 2026)
The objective of this study was to evaluate the effects of in ovo injection of L-arginine on estrogen levels, chick weight, and the development of the bursa of Fabricius in both local and commercial chicken breeds. A total of 240 fertilized eggs were divided into four treatment groups, with varying levels of L-arginine (0%, 1%, 2%, and 3%) administered via in ovo injection on Day 10 of incubation. The eggs were incubated under standard conditions (37.5°C and 60% humidity) until hatching, after which the chicks were raised under controlled conditions. The study focused on assessing chick weight, bursa of Fabricius weight, and serum estrogen levels on Day 14 post-hatch. The results showed no significant differences in chick weight, bursa of Fabricius weight, or relative bursa weight across the treatment groups for both local and commercial breeds. However, significant variations in estrogen levels were observed, with the highest in the 1% L-arginine treatment group (502.55 pg/mL) among local chicks and the lowest in the 2% L-arginine treatment group (195.00 pg/mL). Commercial chicks also exhibited significant differences in estrogen levels, with the highest in the control group (T1) and lower levels in the 1%, 2%, and 3% L-arginine groups. These findings suggest that in ovo L-arginine injection can influence estrogen synthesis, although the effects vary between breeds. The local breed showed a more pronounced estrogen response, highlighting the importance of genotype in nutrient utilization. Overall, although no significant changes in growth or bursa development were observed, L-arginine injection-induced modulation of estrogen may have implications for improving poultry reproductive performance and growth efficiency.